Philippines Economic Update, October 2019 : Resuming Public Investment, Fast Tracking Implementation - World Bank (World Bank, Washington, DC, 2019)
Philippine economic growth slowed to its lowest level in eight years, driven by a rapid deceleration in investment growth in the first half of 2019. GDP growth slowed from 6.3 percent year-on-year (yoy) in the first half of 2018 to 5.5 percent in thesame period in 2019, below government’s growth target of 6-7 percent for 2019. The slowdown was primarily driven by a contraction in nominal public investment due to the delayed passage of the 2019 national government budget and the spending ban on new projects before the May election. Public infrastructure spending shrunk by 15.7 percent yoy in nominal terms, from 5.4 percent of GDP in the first half of 2018 to 4.3 percent of GDP in the same period in 2019. In addition, private investment activities also slowed due to uncertainties around the government’s ongoing tax reform program and the external environment. In this context, private consumption, which regained momentum thanks to declining inflation and improving labor market conditions, was the main driver of growth.